REACHING MATURITY: TEACHING HIGHER EDUCATION STUDENTS POLITICAL SCIENCE IN THE 2020S: Received: 18th September 2021; Revised: 29th March 2022, 1st April 2022, 5th April 2022; Accepted: 13th April 2022 - Duke, Benjamin (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Purpose of the research: This article discusses the different aspects to consider when deciding the pedagogical choices by which various political sciences can be taught and learnt. Pedagogy is the educational process a teacher uses to teach a learner a new skill. Pedagogy can be teacher-centred or learner-centred, the latter focussing on students having an active role in the learning process. Research methodology: This critical review was written by conducting several internet searches using clearly relevant keywords. Grey literature, policy documents from numerous state actors, associated democratisation, higher education practitioners and stakeholders, feature extensively in this critical review. Findings: Political science students could be taught using experiential learning-centred pedagogy, to learn how equality, diversity and inclusion affect political processes. A basic understanding of political science concepts e.g., agenda-setting and media manipulation, are crucial in conceptualising the politic of equality, diversity and inclusion. Conclusions: Three factors that have caused a significant increase in political science degree applications: The 2008 election of Barack Obama as US President heralded digital democracy and E-government participation.; the rise to prominence of Greta Thunberg, climate activist with the environmentalist movement Extinction Rebellion; the #BLM social movement, re-ignited by the death of George Floyd.